Pelaksanaan Pembekalan dan Uji Sertifikasi Tenaga Konstruksi untuk Wilayah Kabupaten Buton Tengah - Muh. Sayfullah. S; Ahmad Efendi; Muhammad Abdu; Aswad Asrasal (PT. Karya Inovatif Nusantara, 2026)
The construction sector plays a strategic role in supporting infrastructure development and regional economic growth. The success of infrastructure development is largely determined by the availability of competent, professional, and certified construction human resources. Central Buton (Buteng) Regency, as a developing region, faces the challenge of limited certified construction workers, both at the skilled and trained levels. In this regard, the Public Works and Spatial Planning Office of Central Buton Regency is holding a competency improvement and certification test for construction workers in collaboration with the Gatesi Karya Konstruksi Professional Certification Institute (LSP) as the Buton Tengah Competency Testing Center (TUK). This community service activity aims to improve the competency, professionalism, and competitiveness of construction workers through a training program and certification test for construction workers in the Buteng region. The implementation method includes identifying competency needs, providing technical and non-technical materials based on the Indonesian National Work Competency Standards (SKKNI), assistance with certification administration, and implementing certification tests carried out through the TUK Sewaktu Buton Tengah mechanism in collaboration with LSP Gatesi Karya Konstruksi licensed by the National Professional Certification Agency (BNSP). The results of the activity showed an increase in participants' understanding of construction service regulations, the implementation of occupational safety and health (K3), and construction work quality standards. In addition, all participants were declared competent and received work competency certificates according to the scheme they followed. This activity contributed positively to improving the quality of regional construction human resources, strengthening the role of local workers in development projects, and supporting the realization of safe, quality, and sustainable infrastructure development in Central Buton Regency.